2022
DOI: 10.1016/j.jhep.2021.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ATG3 ameliorates liver steatosis by increasing mitochondrial function

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…However, recent study by Lima et al reports that unlike mice autophagic activity may be associated in progression of hepatic steatosis in humans. Knockdown of ATG3 in human hepatocyte ameliorated hepatic steatosis condition while overexpression of ATG3 increased lipid load in hepatocytes ( 89 ). This renders possibility that autophagic model may function differently depending on the organism.…”
Section: Sirt1-mediated Autophagy and Endocrine Disordersmentioning
confidence: 99%
“…However, recent study by Lima et al reports that unlike mice autophagic activity may be associated in progression of hepatic steatosis in humans. Knockdown of ATG3 in human hepatocyte ameliorated hepatic steatosis condition while overexpression of ATG3 increased lipid load in hepatocytes ( 89 ). This renders possibility that autophagic model may function differently depending on the organism.…”
Section: Sirt1-mediated Autophagy and Endocrine Disordersmentioning
confidence: 99%
“…9,10 Studies have shown both the lipid metabolism and macrophage related inflammation play an essential role in regulating NASH progression. 11,12 In addition, multiple pathogenic mechanisms, including the glucose and lipid metabolism, bile acid toxicity and hepatic stellate cell activation have been reported to promote progressive liver injury during the progression of NASH. 5 Moreover, the mechanisms of hepatic lipid homeostasis are complex involving lipogenic and lipolytic genes and signaling pathways.…”
Section: Figures Introductionmentioning
confidence: 99%
“…Among these genes, Beclin 1 is usually known as a crucial autophagy marker for the formation of phagophores. Usually, LC3 is linked to lipids or phosphatidylethanolamine to form LC3II, which integrates into the phagophore membrane and plays an important role during autophagy ( Ajazi et al, 2021 ; da Silva Lima et al, 2021 ). Western blot analysis showed that Uro-A enhanced the expression of ULK1, LC3 and Beclin 1 compared with the control group ( Figures 3B,C ).…”
Section: Resultsmentioning
confidence: 99%